HUBUNGAN KEKUATAN OTOT LENGAN-BAHU DAN KELENTUKAN PINGGANG DENGAN SERVICE ATAS BOLA VOLI PADA TIM MTS ALMUTTAQIN PEKANBARU - Muhammad Riski Riski; Saripin '; Kristi Agust Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: the problem in this study originated from the observation that the author found in the field, it turns out students perform less well in the basic techniques of volleyball, as in servicing over. Purpose of this study was to determine the relationship of arm-shoulder muscle strength and flexibility waist with top volleyball serve on a team of MTs Al-Muttaqin Pekanbaru. Population in this study the whole object of research,namely the entire male student who joined the volleyball team MTs Al-Muttaqin Pekanbaru totaling 17 people by using total sampling technique where all the population sampled, to obtain research data used test arm-shoulder muscle strength by the  expanding dynamometer, flexibility waist with bridge-up and servicing over. Data were analyzed by simple and multiple product moment. results obtained from the arm-shoulder muscle strength have been associated with servicing results on volleyball on a volleyball team MTs Al-Muttaqin Pekanbaru.dari waist flexibility results obtained have a relationship to the results of the top volleyball serve the volleyball team MTs Al-Muttaqin Pekanbaru.terdapat jointly relationship between muscle strength and flexibility arm-shoulder waist to serve results on volleyball on a volleyball team MTs Al-Muttaqin Pekanbaru. Keyword: arm-shoulder muscle strength, flexibility waist, servicing over